Prinsip Public Relations dalam Ajaran Islam Menurut Persepsi Anggota Perhumas Jawa Tengah - Trimanah Trimanah; Diah Wulandari (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2018)
Public Relations is a science and also a profession related to the efforts to build a good relationship with publics to gain benefitial mutual understanding. Through such good relationships, a Public Relations Officer (PRO) is required to cultivate a positive image and reputation of the organization in the audience’s mind. In its efforts to provide a good picture and message about the organization, there are principles to be followed by PRO, among others; Tell the truth, Prove it with action, Listen to the customer, Manage for tomorrow, Conduct Public Relations as If the whole company depends on it, Remain calm, Patient and good humored (Arthur W. Page) This principles are in line with the Islamic values as contained in the Qur’an and the hadith of Prophet Muhammad Saw. The members of Perhimpunan Humas (Perhumas) of Central Java who are generally Muslim as a public relations (PR) certainly cannot be separated from what they understand about the principles of goodness in the profession of public relations according to their Islamic religion. Therefore becomes interesting to examine and disclose how their perception on PR principles fit into what they understand in the Islamic values. In an attempt to uncover their perception, a qualitative descriptive approach is used through structured questions of informants that have been determined based on certain considerations which are then analyzed by an interactive analysis model to generate a conclusion.